Crisis Communication in Non-Tectonic Tsunami Disaster Management Policy in Indonesia: The Application of Soft Systems Methodology Based Multi-Method - Akhyar, Dani; Hendriyani, Hendriyani; Hardjosoekarto, Sudarsono (UI Scholars Hub, 2023)
This study aims to discuss disaster crisis communication policies for non tectonic tsunami in Indonesia. The case study was selected from the Sunda Strait tsunami that occurred in December 2018 and claimed more than 400 lives. The disaster is unusual since it is included as a non-tectonic tsunami and unable to be detected by the current tsunami early warning system. This study was conducted at the macro level, namely an analysis of disaster communication policies, specifically Law No. 24/2007 on Disaster Management. The data were collected through big data analysis of the word disaster, textual network analysis of disaster laws, and in-depth interviews with six national disaster stakeholders. The discussion applied Soft Systems Methodology (SSM) based Multi-Method with a combination of Social Network Analysis (SNA) and Textual Network Analysis (TNA) in the stage 2 of SSM, namely compiling a Rich Picture. The application of SSM based Multi-Method has provided a new methodological variant of SSM. The findings of this study contribute to: First, proving the lack of coordination between disaster regulations stipulating several disaster agencies, leading to the faulty operation of the non-tectonic tsunami early warning system. Second, providing recommendations to disaster policy makers to amend Law No. 24/2007. Third, suggesting the transformation of an integrated crisis communication system among national disaster agencies. Fourth, confirming the involvement of Indonesian National Armed Forces (TNI) and Indonesian National Police (Polri) in the process of disseminating information and communication, considering that these two institutions have networks that reach the lowest levels of society. Fifth, proposing the importance of increasing disaster education to disaster stakeholders at the central to regional levels as well as the community on a massive basis, particularly in areas prone to potential disasters.